Wireless sensor network-based health monitoring and smart home assistance for the older adults in sports and wellness towns - Yang, Dapeng; Wang, Junqi; Huang, Li; Wang, Tongling (Frontiers in Public Health, 2024)
Background: Integrating technology with rural development is imperative for addressing the unique challenges faced by aging populations in rural areas. China's national rural revitalization strategy underscores the importance of developing characteristic towns that cater to health and wellness demands, particularly for the elderly. However, there is a gap in the literature regarding the systematic use of technology to support the health and daily living needs of this demographic. Objective: This paper aims to bridge this gap by proposing a wireless sensor network (WSN)-based system that integrates health monitoring and smart home assistance tailored for elderly residents in sports and wellness towns. Methods: The system's design involves the collection and analysis of historical activity data and basic physiological parameters from elderly residents' homes. Data cleaning, fusion, and storage are employed to prepare the data for behavior analysis, which is vital for controlling smart home equipment. Preliminary health assessments are conducted using collected physiological data. A hybrid network leveraging Sub-G and Wi-Fi technologies is optimized for data collection and upload, based on a comparative analysis of wireless communication options. Significance: This study significantly contributes to the advancement of sports and wellness towns by fostering healthy aging through cutting-edge technological solutions.